Menelusuri Makna Senioritas dan Dampaknya Pada Santri di Wilayah JABODETABEK - Khoirini, Fajar Nurisa; Widiasih, Puti Archianti (PAKAR Pendidikan, 2024)
Education is a forum for realizing the intelligent life of the country's children. Islamic boarding schools are one of the educational institutions that can be chosen. Islamic boarding schools not only provide a formal education system but also a religious education system. However, the phenomenon of seniority among students who are part of the education system in Islamic boarding schools certainly needs to be addressed. Santri are students who have responsibility for themselves when studying at an Islamic boarding school, away from parental supervision and living with their friends in a dormitory allowing for seniority among juniors. Seniority is often interpreted as a hierarchy that labels someone as being at a higher level or status. However, seniority is not always positive. Therefore, the aim of this research is to find out junior perspectives regarding the seniority phenomenon and its impact. This research uses a qualitative method using a phenomenological approach. Data that was obtained through observation and interviews with three informants through purposive sampling was then analyzed using interpretative phenomenological analysis (IPA) techniques. The research results showed that juniors experienced both physical and verbal violence and this had an impact on the social attitudes and mental health of the students. This research also found the meaning of seniority from a junior perspective, namely a feeling of wanting to be respected and appreciated, and essentialized as a hereditary culture.